2016
DOI: 10.1373/clinchem.2016.254755
|View full text |Cite
|
Sign up to set email alerts
|

Growth Differentiation Factor 15, Its 12-Month Relative Change, and Risk of Cardiovascular Events and Total Mortality in Patients with Stable Coronary Heart Disease: 10-Year Follow-up of the KAROLA Study

Abstract: BACKGROUND:This study considered whether baseline concentrations and 12-month changes of growth differentiation factor 15 (GDF-15) are associated with subsequent cardiovascular events (CVEs) and total mortality in patients with stable coronary heart disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
17
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 28 publications
4
17
1
1
Order By: Relevance
“…The eligible trials involved a total of 53 706 participants. Six studies enrolled community‐based populations, 17 studies were restricted to patients with coronary artery disease (CAD), five studies were on HF, and the remaining three were respectively pertaining to diabetes mellitus (DM), atrial fibrillation (AF) and intensive care unit patients . The mean age of the subjects ranged from 42 to 79 years.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The eligible trials involved a total of 53 706 participants. Six studies enrolled community‐based populations, 17 studies were restricted to patients with coronary artery disease (CAD), five studies were on HF, and the remaining three were respectively pertaining to diabetes mellitus (DM), atrial fibrillation (AF) and intensive care unit patients . The mean age of the subjects ranged from 42 to 79 years.…”
Section: Resultsmentioning
confidence: 99%
“…Table showed the estimates of association between GDF‐15 levels and risk of adverse outcomes included in the meta‐analysis. Nineteenstudies individually regarded the GDF‐15 level as a continuous variable to evaluate the risk of CVDs, 7 studies only regarded the GDF‐15 level as a categorical variable and 5 studies utilized both two ways. Among the 31 trials, seven reported CVD mortality as outcomes, 13 reported complex adverse outcome, and 20 reported all‐cause mortality as outcomes.…”
Section: Resultsmentioning
confidence: 99%
“…In communitydwelling individuals, higher concentrations of GDF-15 are associated with increased prevalence and incidence of CVD, chronic kidney disease, and cancer, independent of traditional risk factors, renal function, and other biomarkers (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12). GDF-15 has emerged as an independent marker of all-cause mortality, cardiovascular, and noncardiovascular mortality, and nonfatal cardiovascular events in patients with coronary artery disease (13)(14)(15)(16)(17)(18)(19)(20), heart failure (21)(22)(23)(24), and atrial fibrillation (25). GDF-15 is independently associated with major bleeding in patients receiving antithrombotic therapies (20,25) and has been included in a new bleeding risk score, which may become useful for decision support (26).…”
mentioning
confidence: 99%
“…GDF15 был маркером кардиоваскулярных осложнений у больных сахарным диабетом 2-го типа в исследовании KAROLA. Повышение уровня GDF15 предсказывало 10-летнюю сердечно-сосудистую смертность и смертность от всех причин [70].…”
Section: белковые маркеры развития хронической сердечной недостаточноunclassified